Insect pests of Ocimum sanctum Linn. in Karnataka - Manjula, K.N.; Renuka, S.; Rishi , R. Raja; Sundararaj, R. (ENTOMON, 2022)
Survey conducted on Ocimum sanctum Linn. growing in Karnataka revealed the infestation of 16 species of insect pests. Of these, eleven are new records on O. sanctum in Karnataka state.